THE EFFECT OF AUDIT COMMITTEE AND BOARD OF COMMISSIONERS ON AUDIT REPORT LAG - Raditya Ludfianto (Transpublika Publisher, 2023)
Corporate governance has emerged as a vital area of study in ensuring transparency and accountability within organizations. Two key elements of corporate governance are the Audit Committee and the Board of Commissioners. The Audit Committee plays a crucial role in overseeing financial reporting and internal controls, while the Board of Commissioners holds responsibility for strategic decision-making and overall governance. The purpose of this study is to determine the influence of the Audit Committee (X1) and the Board of Commissioners (X2) on Audit Report Lag in Banking Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The research methodology used by the author is descriptive quantitative method. The population used in this study is the banking sector companies. While the data analysis used was the Common Effect Model (CEM) test, Fixed Effect Model (FEM), Random Effect Model (REM), regression test, classical assumptions, and hypothesis testing using the T test (partial) and F test (simultaneous) with using Ms. Excel and Eviews version 12. The results of the research found that the T test hypothesis 1 variable Audit Committee (X2) has an effect on the Audit Report Lag variable (Y), T test Hypothesis 2 the Board of Commissioners variable (X2) has an effect on the Audit Report Lag variable (Y), and the results of the F test show that the variables (X1 & X2) of the Audit Committee and the Board of Commissioners simultaneously affect the variable Audit Report Lag (Y).